Energy Aware Routing for Wireless Sensor Networks - Vidhyapriya, R.; Yu, P. T. VanathiLiguo (INFOCOMP Journal of Computer Science, 2007)
Self organizing, wireless sensors networks are an emergent and challenging technology that is attracting large attention in the sensing and monitoring community. Impressive progress has been done in recent years even if we need to assume that an optimal protocol for every kind of sensor network applications cannot exist. The energy constraint sensor nodes in sensors networks operate on limited batteries, so it is a very important issue to use energy efficiently and reduce power consumption. Many routing protocols have been proposed among these protocols, the adaptive routing protocols are very attractive because they have low routing overhead. As a result, the routes tend to have the shortest hop count and contain weak links, which usually provide low performance and are susceptible to breaks. In this paper we introduce an adaptive routing protocol called energy aware routing that is intended to provide a reliable transmission environment with low energy consumption. This protocol efficiently utilizes the energy availability and the received signal strength of the nodes to identify the best possible route to the destination. Simulation results show that the energy aware routing scheme achieves much higher performance than the classical routing protocols, even in the presence of high node density and overcomes simultaneous packet forwarding.